Study on the promotion of osteo/odontogenic differentiation on SCAPs and anti-inflammatory effects of EGCG/CeO2-loaded nanoparticles in an inflammatory microenvironment - WU Yuting, DAI Mingrui, LENG Diya, ZHU Tingting, WU Tao, WU Daming (Kouqiang yixue)
Objective To investigate the effects of composite nanoparticles E/Ce@MCSNs loaded with epigallocatechin-3-gallate (EGCG) and cerium dioxide (CeO2) on the odonto/osteogenic differentiation of human stem cells from the apical papilla (SCAPs) and macrophage polarization under inflammatory conditions. Methods E/Ce@MCSNs were synthesized and characterized. Cell viability of SCAPs and RAW 264.7 cells treated with varying concentrations of E/Ce@MCSNs was assessed via CCK-8 assay. The antioxidant enzyme-mimetic activity of E/Ce@MCSNs was evaluated. Under simulated inflammatory conditions, intracellular reactive oxygen species (ROS) scavenging capacity was measured via DCFH-DA fluorescent probe. Alkaline phosphatase (ALP) staining/activity, alizarin red staining/semi-quantitative analysis, and RT-qPCR were performed to detect odonto/osteogenic differentiation markers, including dentin sialoprotein (DSPP), ALP, runt-related transcription factor 2 (Runx-2), type Ⅰ collagen (COL-Ⅰ), and osteopontin (OPN) in SCAPs. The effects of E/Ce@MCSNs on the odontogenic/osteogenic differentiation of SCAPs under this condition were evaluated. RT-qPCR were used to analyze cytokine expression (TNF-α, IL-1β, IL-6, iNOS, TGF-β, IL-10) and secreted TNF-α/IL-6 levels in RAW264.7 cells. The concentrations of TNF-α and IL-6 in cell culture supernatants were measured by ELISA. Results E/Ce@MCSNs exhibited excellent biocompatibility at concentrations ≤100 μg/mL. They demonstrated potent ROS-scavenging activity (P<0.05) and significantly enhanced ALP activity (P<0.001), promoted calcium nodule formation (P<0.001), and upregulated odonto/osteogenic gene expression (DSPP, ALP, Runx-2, COL-Ⅰ, OPN) in SCAPs under inflammatory conditions (P<0.05). In RAW264.7 cells, E/Ce@MCSNs downregulated pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, iNOS) (P<0.01) and upregulated anti-inflammatory factors (TGF-β, IL-10)(P<0.001), while reducing TNF-α and IL-6 secretion (P<0.001). Conclusion E/Ce@MCSNs exert antioxidant and anti-inflammatory effects in apical periodontitis by scavenging excessive ROS, thereby promoting odonto/osteogenic differentiation of SCAPs.